2012
DOI: 10.2196/ijmr.2150
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Nurses’ Intention to Use a Computerized Platform in the Resuscitation Unit: Development and Validation of a Questionnaire Based on the Theory of Planned Behavior

Abstract: BackgroundIn emergency department resuscitation units, writing down information related to interventions, physical examination, vital signs, investigations, and treatments ordered is a crucial task carried out by nurses. To facilitate this task, a team composed of emergency physicians, nurses, and one computer engineer created a novel electronic platform equipped with a tactile screen that allows systematic collection of critical data. This electronic platform also has medical software (ReaScribe+) that functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…Only 10 participants were included in the test-retest phase of the study so as to obtain at least 30% of our initial sample as recommended in previous TPB studies. 17,18 Demographic characteristics of the study population was calculated and presented in Table 3. More than 50% of the participants were male with only 2% of the entire population specialized in oncology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 10 participants were included in the test-retest phase of the study so as to obtain at least 30% of our initial sample as recommended in previous TPB studies. 17,18 Demographic characteristics of the study population was calculated and presented in Table 3. More than 50% of the participants were male with only 2% of the entire population specialized in oncology.…”
Section: Resultsmentioning
confidence: 99%
“…10 of the initial participants were approached two weeks later to complete the questionnaire a second time so as to assess the agreement between answers at both times based on the temporal stability criterion. 16,17 The questionnaire was divided into two sections with the first section based on demographic questions and the second based on the key TPB constructs earlier discussed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Işık and Akbolat conducted a study to determine health‐care personnel's level of competence in information technology and reported that 61.8% of them were competent in office programmes, whereas 61.2% were competent in operating systems and 59.2% were competent in operating computer hardware. Malo et al . discovered that nurses' computer literacy level was 2.58 out of a maximum score of 4.…”
Section: Discussionmentioning
confidence: 99%
“…The theory of planned behavior (Ajzen, 1985;Ajzen, 1991) is a widely utilized theory in the healthcare studies, especially when predicting or when assessing the nursing practices (Beduz, 2012;Côté, Gagnon, Houme, Abdeljelil & Gagnon, 2012;Haktanir, 2011;Hassan, Wahsheh & Hindawi, 2009;Javadi, Kadkhodaee, Yaghoubi, Maroufi & Shams, 2013;Malo, Neveu, Archambault, Émond & Gagnon, 2012). This theory was developed from the theory of reasoned action (Azjen & Fishbein, 1980) with little differences between them.…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%